PRIMEIRO EU: empoderamento de Agentes Comunitários para o protagonismo na promoção da Saúde. - Nakatani, Janete (2014)
The Community Health Agent in the family health strategy and its competence or lack thereof, in the development of health promotion actions, has been the focus of constant reflections and studies. Whereas competence as: "knowing, know-how and knowing how to be", we observe that these professionals are so diseased as those whom they propose to handle. Believing it to be possible to empower them to better care for themselves, consequently, making it the best caretakers of others, we proposed the intervention- -"First I: empowerment of community agents for the role in health promotion". An opportunity to stop, look at you, analyze your actions and conceptions of the cuddle up, reflecting on health promotion, rebuilding and resignificando knowledge and individual supremacy. Participated in this intervention, 13 ACS members of two teams of the family health strategy the Health Center Dr. Antonio Guanaré, located in the sanitary district, municipality of São Luís Coroadinho, MA. We held six meetings, with five of them leadership workshops, named: I and my belly button; I Me Hunter; Behold and Watch all of you; Mirror, mirror, there's no better Caregiver of Me than me?; D-day I. In these workshops, active methodologies have been proposed such as: interviews, group dynamics, dispersion and construction activities of individual records in logbooks. The most obvious results of this craving to experience different, perceived in the logs and observed behaviors, was the expansion of self knowledge and reflection of the situation of individual health and its relationship with the leading role in health promotion, the need to plan better and plan for the care of themselves with the details of time and frequency of execution, the construction of an individual care plan based on survey and mapping of risks and co-morbidities.